2017
DOI: 10.1177/0269216317717370
|View full text |Cite
|
Sign up to set email alerts
|

Moving on: Factors associated with caregivers’ bereavement adjustment using a random population-based face-to-face survey

Abstract: These results support the relevance of 'moving on' as an indicator of caregivers' bereavement adjustment. Following the outcomes of bereaved caregivers longitudinally is essential if effective interventions are to be developed to minimise the risk of prolonged grief disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…2 Emotional support is also necessary for MND caregivers because of their much higher risk of PGD than the general bereaved population and insufficient support for caregivers during the disease journey was a significant predictor to PGD. 2 Support helps caregivers to move on, 22 but this study showed that the support received was not optimal. This dissatisfaction was closely linked to the perception that staff lacked training and competence in this area of care, which was compounded by insufficient contact with Advisors.…”
Section: Training For and Provision Of Emotional Supportmentioning
confidence: 80%
“…2 Emotional support is also necessary for MND caregivers because of their much higher risk of PGD than the general bereaved population and insufficient support for caregivers during the disease journey was a significant predictor to PGD. 2 Support helps caregivers to move on, 22 but this study showed that the support received was not optimal. This dissatisfaction was closely linked to the perception that staff lacked training and competence in this area of care, which was compounded by insufficient contact with Advisors.…”
Section: Training For and Provision Of Emotional Supportmentioning
confidence: 80%
“…Caregiver prolonged grief (PG-12) predicted post-death prolonged grief (PG-13) scores, and this finding aligns with previous studies showing the predictive utility of the PG-12. 8,[19][20][21] However, several factors contribute to prolonged grief symptoms post-death, 20,22,[25][26][27] which is why comprehensive, systematic and repeated assessment of grief, both before and after death, is recommended in research, 20,23,46,47 policy 48 and practice guidelines. 49 Preand post-death support that is tailored to the needs of 'normal' grievers, who are the majority of bereaved caregivers, might best work in partnership with explicit and careful attention to promoting informal support, 50 and could focus on bereaved caregivers' wishes for more information on preparing for bereavement, how to harness their social networks and developing strategies for dealing with grief.…”
Section: Discussionmentioning
confidence: 99%
“…a closer relationship to the deceased, socioeconomic disadvantage) as well as positive factors for reduced risk (e.g. positive high-quality social support, caregiver report of needs met) [ 35 39 ]. Moreover, instruments to identify family members at risk for developing bereavement-related mental health challenges pre- or post-loss have been developed (e.g.…”
Section: Discussionmentioning
confidence: 99%